An Assessment of Point-of-Care PCR Testing for the Diagnosis and Management of Meningo-Encephalitis. Issue 2 (28th February 2020) - Gamio-Izasmendi, Diana; Cooke, Benjamin
Abstract : BACKGROUND Meningitis and Encephalitis are potentially fatal infections. When suspected, empirical treatment is started, and only safely discontinued once excluded. The impact of current CSF investigations is prolonged inpatient stay, and exposure to broad-spectrum antimicrobials. Biofire Filmarray is a point-of-care PCR system. Our aim was to assess time to BioFire result, and its impact on clinical management. METHOD BioFire was implemented, in addition to current practice, on CSF samples with WCC ≥10 and all neonatal samples processed between November 2018 and February 2019. Data was collected prospectively for: patient demographics, sampling time, time to result of BioFire and current PCR, antimicrobial regime, and early discharge. Percentage agreement between BioFire and current PCR, mean time to result, percentage cases with reduction in antimicrobials, and mean length of stay for those discharged based on BioFire, were calculated. RESULTS There were 22 samples analysed. There was an 86.4% agreement between BioFire and current PCR. In cases of disagreement, BioFire identified pathogens where standard PCR had not. One sample was insufficient for virology PCR however, a full array was obtained from BioFire. Mean time to BioFire result authorization was 17.8 hours, compared to 316 for virology PCR and 331.2 for bacteriology PCR. BioFire allowed narrowing of antimicrobial therapy in 22.7% of patients, discontinuation in 41.0%, and early discharge in 27.3%. CONCLUSION BioFire provides comparable diagnosis of meningo-encephalitis faster than current practice. With the current focus on rising bed pressures and antimicrobial stewardship, BioFire allows targeted therapy and safe early discharge where infection is excluded.